2016
DOI: 10.4209/aaqr.2015.07.0445
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Anthropogenic Gases: Nitrogen Oxides, Sulfur Dioxide, Ozone and Ammonia in Kathmandu Valley, Nepal

Abstract: Kathmandu Valley is one of the largest and most polluted metropolitan regions in the Himalayan foothills. Rapidly expanding urban sprawl and a growing fleet of vehicles, and industrial facilities such as brick factories across the valley have led to conditions where ambient concentrations of key gaseous air pollutants are expected to exceed Nepal's National Ambient Air Quality Standards (NAAQS) and World Health Organization (WHO) guidelines. In order to understand the spatial variation of the trace gases in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 48 publications
1
34
0
1
Order By: Relevance
“…To our knowledge, this is the first comprehensive study of wide spatial and temporal variation in PM 2.5 pollution, notably PM 2.5 chemical composition, in the Kathmandu Valley, and it builds upon related work Kiros et al, 2016) on anthropogenic air pollution exposure and health effects in this community.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first comprehensive study of wide spatial and temporal variation in PM 2.5 pollution, notably PM 2.5 chemical composition, in the Kathmandu Valley, and it builds upon related work Kiros et al, 2016) on anthropogenic air pollution exposure and health effects in this community.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as mentioned above, the emissions from biomass co-fired brick kilns increased in Period II after 4 January 2013 (Sarkar et al, 2016). Previous studies reported that the concentrations of PM 10 , particulate carbon, SO 2 , NO x , and volatile organic compounds increased considerably when nearby brick kilns were operating (Raut, 2003;Pariyar et al, 2013;Kiros et al, 2016;Sarkar et al, 2016Sarkar et al, , 2017. The comparison of the aerosol properties observed in the Kathmandu Valley with those reported in previous studies in East and South Asia is given in Fig.…”
Section: Surface Aerosol Optical and Chemical Properties During The Smentioning
confidence: 90%
“…In addition, the Kathmandu Valley is located downwind of the Indo-Gangetic Plain region that experienced rapid growth in emissions and severe air quality degradation. All of this has resulted in elevated air pollution concentrations, especially during the dry season (Sapkota and Dhaubhadel, 2002;Shrestha and Shrestha, 2005;Sharma et al, 2012;Kiros et al, 2016). In addition, the bowl-shaped structure of the Kathmandu Valley, with a bottom altitude of ∼ 1.3 km and a rim of 2 to 2.8 km, and topography-induced circulations have made the air pollution more serious by limiting the transport of air pollutants out of the valley (Regmi et al, 2003;Panday and Prinn, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this, the Ozone Monitoring Instrument (OMI) provides the scientific community with a valuable source of information since it is the first space-borne hyperspectral ultraviolet/visible spectrometer that enables a continuous mapping of several trace gases and ozone, including SO 2 and NO 2 , globally and on a daily basis [19]. There have been an increasing number of studies related to NO x and SO x emissions in the last decade [10,13,[20][21][22][23][24][25]. However, few of them were devoted to analysing linear and non-linear trends in the Southern Hemisphere (SH), and those papers dealing with this particular topic only studied specific locations [26].…”
Section: Introductionmentioning
confidence: 99%